Pengembangan E-Modul Berbasis Flip Pdf Professional Subtema Lingkungan Tempat Tinggalku - Devia Sri Ramadhanti; Tustiyana Windiyani; Santa Santa (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The application of technology according to the needs of students is flexibility and optimal learning. Facts in the field that students feel bored with textbook themes resulting in a lack of attention to learning, learning does not vary, and inadequate time. E-Modules are made to help understand learning in an interesting way and use flexible study time. The aim of the research is to develop the E-Module and test the eligibility of the E-Module. This study uses research and development methods (Research and Development), the research procedure used is the ADDIE model. The validation test stage for the E-Module, namely media experts, material experts, and linguists with all criteria, is very feasible to be tested on students in using the E-Module. the results of using the E-Module with very feasible criteria. The conclusion obtained is that the development of E-Modules using the Flip PDF Professional application is stated to be very feasible to develop and can be used in the learning process by students.Â